Maternal and neonatal outcomes in pregnancies complicated by heart disease: a 5-year retrospective study at a tertiary center hospital in Klang Valley, Malaysia - Abdul Hamid, Habibah; Paramasivam, Karthini; Mohamad Hamsan, Ameerah Izzati; Rejali, Zulida (BP International, 2024)
Maternal heart disease is a leading cause of indirect maternal mortality worldwide similarly in Malaysia with substantially increment in heart disease related.